Federalismo e tributação : análise do imposto de renda retido na fonte sob a perspectiva da repartição constitucional das receitas tributárias - Montovani Filho, Jair Cortez (2016)
This paper approaches the issue of income tax with holding and its repercurssions against Brazilian constitucional law. At firts, we discuss the concept of fiscal federalism and the developments of case law on the subject, more precisely the locus standi of the member State of the Federation in action replay undue tax. Afterwards, we report a change in a position of Brazilian National Treasury und IRS regarding the metodology of calculating the tax due, which directly affects state revenues. As a response to such situation, we suggest the conclusion that the lack of technicality of the constitutional text distouted the rule of income tax, creating and apparent paradox, which can be solved from the systematic interpretation of the Constitution